Archetype, Urphänomen and Polarity: Aesthetic Considerations on Nature, Art, and Life Between Goethe’s Morphology and Taoism - Giacomelli, Alberto (Aesthetica Preprint, 2021)
In his scientific works, Goethe elaborates a morphology of nature based on a dynamic, organic and anti-essentialist conception of life and its forms. To clarify what Goethe means by “morphology” in both natural and artistic spheres, I mean to show the specificity of such fundamental notions as “archetype”, “original phenomenon”, “form” and “formation”. I will then explain how Goethe’s morphology is closely linked to the notion of “polarity”, referring in particular to Faust. In the second part of the paper, I will develop a cross-cultural comparison between Goethe’s morphology and Taoist thought. Then I will highlight some similarities and differences between the ‘classical’ Chinese landscape painting of Shitao and the and the Goethe-influenced painting of Carl Gustav Carus.